Multiple Levels of Meaning: Three Current German Picturebook Versions of Fairytales by the Brothers Grimm - Bettina Kümmerling-Meibauer (Strenae)
This chapter focuses on three German picturebook versions of fairytales by the Brothers Grimm which were published in the 21st century. A short introduction provides an overview on the reception and illustration of the Grimms’ fairytales in Germany in the 19th and 20th centuries. Against this background, this contribution demonstrates that the selected picturebooks use different artistic techniques and styles in order to carve out the hidden potential of the original fairytale versions, thus adding new levels of meaning. Sybille Schenker’s Rotkäppchen (2014) uses the silhouette technique to point to the issues of disguise and deception, while Susanne Janssen’s Hänsel und Gretel (2007) applies collages of photos and acrylic painting to stress the difference between reality and imagination. Finally, Jonas Lauströer’s colored pencil drawings in Von dem Fischer und seiner Frau (2013) highlight an ecological perspective, as they call attention to environmental pollution caused by human greed and carelessness.